Hypogonadism induced by surgical stress and brain trauma is reversed by human chorionic gonadotropin in male rats: A potential therapy for surgical and TBI‐induced hypogonadism?. Issue 3 (18th March 2021) - Geddes, Rastafa I.; Kapoor, Amita; Hayashi, Kentaro; Rauh, Ryan; Wehber, Marlyse; Bongers, Quinn; Jansen, Alex D.; Anderson, Icelle M.; Farquhar, Gabrielle; Vadakkadath‐Meethal, Sivan; Ziegler, Toni E.; Atwood, Craig S.
Abstract: Introduction: Hypogonadotropic hypogonadism (HH) is an almost universal, yet underappreciated, endocrinological complication of traumatic brain injury (TBI). The goal of this study was to determine whether the developmental hormone human chorionic gonadotropin (hCG) treatment could reverse HH induced by a TBI. Methods: Plasma samples were collected at post‐surgery/post‐injury (PSD/PID) days ‐10, 1, 11, 19 and 29 from male Sprague‐Dawley rats (5‐ to 6‐month‐old) that had undergone a Sham surgery (craniectomy alone) or CCI injury (craniectomy + bilateral moderate‐to‐severe CCI injury) and treatment with saline or hCG (400 IU/kg; i.m.) every other day. Results: Both Sham and CCI injury significantly decreased circulating testosterone (T), 11‐deoxycorticosterone (11‐DOC) and corticosterone concentrations to a similar extent (79.1% vs. 80.0%; 46.6% vs. 48.4%; 56.2% vs. 32.5%; respectively) by PSD/PID 1. hCG treatment  returned circulating T to baseline concentrations by PSD/PID 1 (8.9 ± 1.5 ng/ml and 8.3 ± 1.9 ng/ml; respectively) and was maintained through PSD/PID 29. hCG treatment significantly, but transiently, increased circulating progesterone (P4 ) ~3‐fold (30.2 ± 10.5 ng/ml and 24.2 ± 5.8 ng/ml) above that of baseline concentrations on PSD 1 and PID 1, respectively. hCG treatment did not reverse hypoadrenalism following either procedure. Conclusions: Together, these data indicate that (1) craniectomy is sufficient to induce persistent hypogonadism and hypoadrenalism, (2) hCG can reverse hypogonadism induced by a craniectomy or craniectomy +CCI injury, suggesting that (3) craniectomy and CCI injury induce a persistent hypogonadism by decreasing hypothalamic and/or pituitary function rather than testicular function in male rats. The potential role of hCG as a cheap, safe and readily available treatment for reversing surgery or TBI‐induced hypogonadism is discussed. Abstract : Traumatic brain injury (TBI) is a major public health problem that induces hypogonadism and exacerbates the length of recovery. We find that craniectomy or TBI in male rats induces a persistent hypogonadism that can be reversed using the developmental hormone human chorionic gonadotropin (hCG). hCG is a cheap and readily available FDA‐approved drug that could be a safe treatment for reversing hypogonadism and improving recovery from brain trauma.